TiO2–NGQD composite photocatalysts with switchable photocurrent response. Issue 6 (20th January 2023) - Lawrence, Reece T.; Croxall, Mark P.; Lu, Cheng; Goh, M. Cynthia
Abstract : A series of titanium dioxide–nitrogen doped graphene quantum dot (TiO2 –NGQD) composite photocatalysts were synthesized through a simple hydrothermal reaction with varied NGQD content. Abstract : A series of titanium dioxide–nitrogen doped graphene quantum dot (TiO2 –NGQD) composite photocatalysts were synthesized through a simple hydrothermal reaction with varied NGQD content. Through a proposed Z-Scheme heterojunction, the composites were able to achieve increased photocurrent generation and photocatalytic degradation of phenol under both full spectrum and visible only illumination. The prepared composites were able to switch from anodic to cathodic photocurrent by changing the light source from full spectrum to visible wavelengths. The photocatalytic capabilities of the composites were tested by degrading phenol and this was monitored via nuclear magnetic resonance. All composites outperformed the commercial standard P25 TiO2 under both full spectrum and visible irradiation, with the 8 wt% NGQD composite showing a visible improvement of over 600% compared to P25. With the ability to manipulate the generation of majority charge carriers, TiO2 –NGQDs have significant potential not only in photocatalysis, but in far reaching applications such as energy harvesting and water splitting.